Empirically supported treatments. An approach to your benefits, limitations and suggestions for improvement - Primero, Gerardo (2011)
In this paper we carry out a review about the Empirically Supported Treatment movement, pointing out its principal advantages and disadvantages and analyzing improvement proposals. In the first part of the article we introduce the topic, providing a historical perspective. Secondly, we focus on our main concerns: lack of coordination between research and its applications in the field, limitations when using the international classifications of mental disorders, standardization of treatment guidelines and differences between levels of evidence. Finally, the main proposals to overcome these limitations are discussed in order to improve the study of efficient psychological treatments of both mental and nonclinical psychological problems.